(3eONd TGeds - (3NGdO(B, (3ebGHdgs ((3YeGf(B:s (3OGQ RgQGf(B,s, 2009)
(3JShb GdNOeGJ h GdJShjb GdafObj , GdJfXje GdJShjbj , eRjL GdNOedJ GdafObjI , GdJSYjQI h GdJhRjY h GdJQhjL , GdCaQGO , GdeTGcd GdJShjbjI aj GdUfGYI GdafObjI eY hLhO eUWdMGJ gGeI aj GdSjGMI h GdafObIs
(3eQGLY U(B.247s
Keywords: (3GdJShjbs; (3GdSjGMIs; (3GdafGObs; (3GdafGOb `` JShjbs